Syllogism as a Framework for Thinking in PAI Learning: Analysis of Implementation on the Materials of Aqidah, Akhlaq, and Fiqh - Wayan Gastiadirrijal; Syifa Samrotul Fauziyah; Muhamad Parhan (ANWARUL, 2025)
This study examines the integration of syllogism—a deductive reasoning framework originating from Aristotle—into Islamic Education (Pendidikan Agama Islam/PAI), specifically within Aqidah (creed), Akhlaq (morality), and Fiqh (jurisprudence) to foster rational and reflective learning. The objective is to demonstrate how syllogistic reasoning enables students to move from dogmatic acceptance toward a logically grounded understanding of Islamic faith, ethics, and law. Employing a qualitative literature review methodology, the research synthesizes classical Islamic texts (including works on qiyas) and contemporary pedagogical scholarship, which are analyzed descriptively to map conceptual linkages between syllogism and PAI learning domains. The findings indicate that in Aqidah, syllogism strengthens faith in tauhid (monotheism) by structuring rational argumentation through premise-based inference; in Akhlaq, it connects faith to moral conduct by formulating ethical syllogisms that clarify the logical basis of virtuous behavior; and in Fiqh, it parallels qiyas by deriving specific legal rulings from general principles and universal evidences. Collectively, these applications show that syllogism can balance cognitive rigor with spiritual depth, rendering PAI more critical, dialogical, and contextually relevant. The study concludes that syllogism offers an integrative pedagogical model for contemporary Islamic education that supports the holistic development of individuals who are faithful, knowledgeable, and morally upright.